The Recent Behavior of U.S. Trade Prices. (IMF Working Papers; Working Paper, 1989)
There is a widespread view that the adjustment of U.S. trade prices--and hence merchandise trade flows--in the face of the substantial dollar depreciation since early 1985 has been slower than might have been expected. This paper examines the recent behavior of U.S. trade prices, and concludes that the modest movements are largely attributable to a decline in computer prices, swings in commodity prices, and the growing importance of computers in U.S. trade. Empirical results suggest that once the influence of computer and commodity prices are taken into account, the recent behavior of U.S. trade prices is not out of line with historical experience.